2018
DOI: 10.1186/s12879-018-3579-6
|View full text |Cite
|
Sign up to set email alerts
|

Gonorrhea and chlamydia prevalence in different anatomical sites among men who have sex with men: a cross-sectional study in Guangzhou, China

Abstract: BackgroundA high rectal and oropharyngeal sexually transmitted infection (STI) burden has been reported among men who have sex with men (MSM) in many regions, but little data exists on rectal and oropharyngeal STIs among MSM in China. The purpose of this study was to determine the prevalence of gonorrhea and chlamydia at different anatomic sites among MSM in Guangzhou, China.MethodsWe recruited a cross-sectional sample of MSM in one Chinese city and collected detailed information about socio-demographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 22 publications
(14 reference statements)
3
30
3
1
Order By: Relevance
“…This is similar to treating cervical infection (CT/NG) in the vaginal discharge flowchart. The limitations are thus similar with rectal infections, where the majority are asymptomatic . In a small study in Kenya, one in five men with an anorectal CT/NG reported rectal pain ; in Côte d'Ivoire, more than half of the men in the study reported anorectal symptoms in the past 12 months ; in Germany, 12% of 2247 men who have sex with men (MSM) had anorectal CT/NG, and only 12% of these had local symptoms, and 91% of both rectal and pharyngeal CT/NG would have been missed if only symptomatic men had been tested .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This is similar to treating cervical infection (CT/NG) in the vaginal discharge flowchart. The limitations are thus similar with rectal infections, where the majority are asymptomatic . In a small study in Kenya, one in five men with an anorectal CT/NG reported rectal pain ; in Côte d'Ivoire, more than half of the men in the study reported anorectal symptoms in the past 12 months ; in Germany, 12% of 2247 men who have sex with men (MSM) had anorectal CT/NG, and only 12% of these had local symptoms, and 91% of both rectal and pharyngeal CT/NG would have been missed if only symptomatic men had been tested .…”
Section: Resultsmentioning
confidence: 91%
“…Additionally, the cause of genital ulcer disease (GUD) syndrome has become less by chancroid or syphilis and more by herpes simplex virus (HSV) . With the advent of molecular tests, it has become evident that many more infections exist asymptomatically in both men and women and that the diagnostic accuracy of STI syndromes is low . In addition, the increasing rates of antimicrobial resistance (AMR) in NG and Mycoplasma genitalium (MG) with limited treatment options make it imperative that treatments are based on aetiological diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of CT (10.1%) and NG (8.6%) in our study were lower than for MG, but still high, and comparable to other studies among MSM, especially in Western countries. Globally, prevalences varied between 1 and 24% for CT, and 0 and 54% for NG [8,11,[44][45][46][47][48][49][50][51][52][53][54][55], depending on the type of the recruiting institution, clinical symptoms, HIV status and sexual behaviour of the participants. Extragenital as well as asymptomatic infections were reported to be common.…”
Section: Sti Prevalencesmentioning
confidence: 99%
“…As expected, test positivity was highest among MSM attending STI clinics: 35% among 229 STI clinic attendees in Guatemala and 22% among 463 men in Guangzhou, China (including 7.2% rectal positivity and 3.9% pharyngeal positivity). 25,26 In over 10 000 MSM tested in 42 STI clinics in the USA during 2010-12, 11.1% tested positive for urethral gonorrhoea, 10.2% tested positive for rectal gonorrhoea and 7.9% tested positive for pharyngeal gonorrhoea. 27 Much lower test positivity was found among MSM who were enrolled in cohort studies or sampled through respondent-driven sampling in Brazil, Thailand, coastal Kenya and Uganda; 1.4-1.8% had urethral gonorrhoea, 1.8-9% had rectal gonorrhoea and 0.5% pharyngeal gonorrhoea at baseline.…”
Section: Gay Bisexual and Other Men Who Have Sex With Menmentioning
confidence: 99%